Most important foliar diseases of strawberry cultivation in the Pamplona area (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2021)
The aim of the research was to identify the most important foliar diseases of strawberry in the municipality of Pamplona and to determine their incidence and severity by varieties and villages. The work was carried out in six villages in the municipality of Pamplona Norte de Santander: Chíchira, Jurado, Monteadentro, El Rosal, Altograndre and Cariongo from March to August 2020. The most important foliar diseases of strawberry in the studied Veredas were Ramularia tulasnei, Colletotrichum sp., Botrytis cinerea and Xanthomonas fragariae. The incidence of anthracnose on the foliage did not differ between the different villages, but on flowers it was higher in the villages Jurado, Chíchira and Cariongo, and on fruits it was higher in the Veredas Jurado and Cariongo. The incidence of Ramularia tulasnei spot was higher in Jurado and Cariongo and B. cinerea rot in fruits was higher in Jurado, Altograndre and Cariongo, while Xanthomonas leaf spot was higher in Altograndre and Cariongo. The Festival variety stood out for having low levels of incidence of all diseases in foliage, flowers and fruits, followed by the Sabrina and Camino Real varieties, while it also stood out for the low severity index of Ramularia tulasnei leaf spot.
Keywords: Fragaria x ananassa; pathogens; fungi; bacteria; varieties